ANALISIS EFISIENSI PENGGUNAAN ARANG TEMPURUNG KELAPA DAN GAS ELPIJI 3 KG UNTUK BAHAN BAKAR MEMASAK RUMAH TANGGA DI KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Umar '; Azwar Harahap; Deny Setiawan (Jurnal Ekonomi, 2013)
The research was done because people dilemma will used coconut shell charcoaland 3 kg LPG gas for household cooking fuel in Enok subdistrict Indragiri Hilir.So the purpose of this study is to find out which one is more efficient use ofcoconut shell charcoal or 3 kg LPG gas for household cooking fuel.This study used non-probability sampling technique in which members of theselected sample, taked base on rashness discover respondents who needed, suchas easy to find or reach and obtained 100 respondents from the samplingtechnique Slovin formula. The analysis method used is descriptive research thatdiscuss set of problems research with describing and explain based on that resultby the interpreted with the relevant theoriessoacanadescribeatheasituation. Fromresult of the research had done concluded that more efficient use of 3 kg LPGgas for household cooking fuel compared with using coconut shell charcoalbecause people in Enok subdistrict Indragiri Hilir felt the price of coconut shellcharcoal more enough expensive. However, there are a lot of people who still usecoconut shell charcoal for several reasons of descend culture.Kata Kunci : coconut shell charcoal, efficiency, 3 kg LPG.